Nuevos registros de Anambé Verde (Pachyramphus viridis) (Passeriformes, Tyrannidae) en Uruguay - González, Enrique M.; Geymonat, Giancardo; Calimares, Carlos (Nuestras Aves, 2001)
Este artículo no cuenta con un resumen.